The Determination of Monthly Premium of Joint Term Health Insurance for Hospital Care - Darma Ekawati (Universitas Bumigora, 2020)
Hospital care is one of the insurance products giving compensation to the members by reimbursing the medicine and hospital care costs. According to the number of members in one insurance policy, health insurance is classified into two categories namely individual health insurance and joint health insurance. This article discusses the monthly premium of joint health insurance. The monthly premium of joint term health insurance is calculated before deciding the probability to facilitate hospital care for two or more people using The RP-2000 Combined Healthy Tables and joint life annuity. Based on the simulation, at the same benefit, the monthly premium that must be paid for joint health insurance is smaller than for individual health insurance because the premium for joint insurance are borne by some insured under the same insurance policy